1989
DOI: 10.1128/jb.171.6.2919-2924.1989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the enzymatic basis for delta-aminolevulinic acid auxotrophy in a hemA mutant of Escherichia coli

Abstract: The hemA mutation of Escherichia coli K-12 confers a requirement for delta-aminolevulinic acid (ALA). Cell extract prepared from the hemA strain SASX41B was incapable of producing ALA from either glutamate or glutamyl-tRNA, whereas extract of the hem+ strain HB101 formed colorimetrically detectable amounts of ALA and transferred label from 1-[14C]glutamate and 3,4-[3H]glutamyl-tRNA to ALA. Extracts of both strains converted glutamate-1-semialdehyde to ALA and were capable of aminoacylating tRNAGlu. Glutamyl-tR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
51
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…The E. coli hemA gene was cloned and sequenced simultaneously by three groups (Drolet et al, 1989;Li et al, 1989;Verkamp and Chelm, 1989). The study demonstrating the C5 pathway in E. coli also showed that Glu-tRNA synthetase and GSA-aminotransferase activities were present in the mutant strains, and that in vitro 5-aminolevulinic acid synthesis could be rkstored by addition of Chlorella vulgaris GlutRNA reductase to the mutant extracts (Avissar and Beale, 1989). Thus the 5-aminolevulinic acid auxotrophy in hemA mutants is caused by the absence of Glu-tRNA reductase activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The E. coli hemA gene was cloned and sequenced simultaneously by three groups (Drolet et al, 1989;Li et al, 1989;Verkamp and Chelm, 1989). The study demonstrating the C5 pathway in E. coli also showed that Glu-tRNA synthetase and GSA-aminotransferase activities were present in the mutant strains, and that in vitro 5-aminolevulinic acid synthesis could be rkstored by addition of Chlorella vulgaris GlutRNA reductase to the mutant extracts (Avissar and Beale, 1989). Thus the 5-aminolevulinic acid auxotrophy in hemA mutants is caused by the absence of Glu-tRNA reductase activity.…”
Section: Discussionmentioning
confidence: 99%
“…5-aminolevulinic acid requiring mutants in E. coli were divided into two classes corresponding to mutations in two loci termed hemA (Sasarman et al, 1968) and hemW(popC) (Powell et al, 1973) both claimed to encode 5-aminolevulinic acid synthase. This apparent discrepancy was explained, when it was discovered that E. coli synthesizes 5-aminolevulinic acid from glutamate by the threestep C5 pathway (Avissar and Beale, 1989). The hemL gene was shown to encode GSA-aminotransferase (Grimm et al, 1991), while the function of the hem4 gene remained unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one route, used by animals, yeast, and bacteria such as Rhodobacter and Rhizobium, a single enzyme condenses glycine with succinyl-CoA to produce 6- (3). Additionally, the conversion of glutamate to 6-aminolevulinate in extracts of the hemA mutant was restored in vitro by the addition of crude preparations of the reductase from Chlorella (4). Sequencing the first 18 amino acids from the N terminus of the reductase purified from barley chloroplasts provided the proof that the hemA gene codes for the glutamyl tRNAGlU reductase (5).…”
mentioning
confidence: 98%
“…The E. coli hemA gene has been cloned by complementation of the original hemA strain by several groups (11,22,42), and homologous hemA genes have been isolated from S. typhimurium (13) and B. subtilis (33). Although direct biochemical evidence for the function of HemA has not been reported, reconstitution experiments with extracts of mutant strains implicates HemA at the level of Glu-tRNAG"u conversion to GSA by the Glu-tRNA reductase (3,4). The original E. coli popC mutants have perished (27a), but the hemL locus of S. typhimurium appears to be analogous (13,14).…”
mentioning
confidence: 99%